Hegyi competition index decomposition to improve estimation accuracy of Larix olgensis crown radius - Zhao Sun; Yifu Wang; Lei Pan; Yujun Sun (Ecological Indicators, 2022)
The current individual tree competition indexes cannot provide information on the competitive pressure of trees in different directions. To quantitatively describe the magnitude of competitive pressure on trees in different directions, this study proposes a method to calculate the magnitude of competitive pressure in the east, west, south, and north directions based on the Hegyi competition index. The Hegyi competition index was assumed as a vector and it is decomposed in two vertical directions by attributing a weight in each direction. Under the condition that the Hegyi index is constant, the Hegyi index is allocated to the four directions. Correlation analysis between the Hegyi competition index components in the four directions of trees and the crown radius of the corresponding azimuth was carried out. The crown radius prediction model containing the Hegyi competition index component was established by using Generalized additive models (GAMs). The results show that the Hegyi competition index component was significantly negatively correlated with the crown radius in the corresponding direction, and the correlation coefficient with the crown radius in the corresponding direction was the largest compared with other directions. The crown radius in the four directions decreased with the increase of the Hegyi competition index component in the corresponding direction, indicating that the competition pressure on the crown in a specific direction inhibited the growth and extension of the crown in this direction. After adding the Hegyi competition index component, the fitting effect of crown radius models in different directions is greatly improved. In general, the Hegyi competition index component quantitatively expresses the competitive pressure of trees in different directions. The proposed method has particular significance for the study of tree crown morphology and provides a new idea for studying the competitive growth relationship of plants.